Needs Analysis and Development of Pharmacy Management Information Systems - Nurul Huda; Jason Merari Peranginangin; Tri Wijayanti (GLOBAL HEALTH SCIENCE GROUP, 2026)
Pharmacy management in Blora Regency, Central Java, is dominated by manual systems such as stock recording in ledgers, causing inventory errors, transaction delays, and the risk of expired drugs. With 300 pharmacies serving 1 million people in rural areas, the problem is exacerbated by limited digital infrastructure and real-time BPOM-JKN regulatory requirements, as well as the impact of the COVID-19 pandemic. As many as 65% of pharmacies in Central Java are not yet computerized, resulting in 15-25% of stock wastage. This study aims to: (1) analyze the needs of pharmacy management information systems (SIM); (2) design and develop SIM based on UML and the DeLone-McLean model; (3) compare the satisfaction of respondents with existing SIM versus new SIM. The quantitative positivism approach involved 22 pharmacists who own pharmacies in Blora (systematic sampling), a 1-5 Likert questionnaire, observation, a 7-day prototype test, and SPSS 25 analysis (validity, reliability, Kolmogorov-Smirnov, paired t-test/Wilcoxon). Feature priorities included purchase/return reports (77.3%) and user access (77.3%). The post-test showed significant improvements: system quality (31.8%→86.4%), information (36.4%→81.8%), service (45.5%→86.4%), usage (50%→90%), satisfaction (45.5%→86.4%); temporary benefits decreased (45.4%→31.8%). The new SIM increases efficiency by 40-50%, accuracy by 95%, saves 50% of time, and supports compliance with Minister of Health Regulation No. 73/2016. Recommendations include training for the Health Office, BPJS integration, and AI stock prediction for rural replication.